Photosynthetic performance and leaf water potential of gulupa (passiflora edulis sims, passifloraceae) in the reproductive phase in three locations in the colombian andes (2015)
Gulupa, Passiflora edulis Sims (Passifloraceae), is an important fruit due to its organoleptic and nutritional characteristics and its demand in the international market; however, very few studies have been conducted for study its Ecophysiology. Until now, this crop has spread throughout the country through empirical knowledge without data that indicate the zones that are more suitable for its cultivation. For this reason, gas exchange, chlorophyll fluorescence (photosystem II operating efficiency and maximum quantum efficiency of photosystem II photochemistry) and leaf water potential were measured in three different locations of Cundinamarca department (Chia [2610 m a.s.l., 14 °C], Granada [2230 m a.s.l., 15 °C] and Tena [2090 m a.s.l., 17 °C]), whose climatic conditions were monitored with meteorological stations to evaluate the physiologic performance in each location related to the environmental factors. The results indicate that, even though the photosynthetic capacity was similar and high in Granada and Tena, the water status of the plant, the stomatal control of water loss and recovery of photosystems during the night were more efficient in Granada (p 0.05). In Tena, the small differences between day and night temperature, humidity, and vapor pressure deficit (VPD) limited the night water recovery in the plants. Meanwhile, in Chia, the increase of VPD during the day and the low temperatures decreased the water potential both during the day and during the night, as well as the recovery of photosystem II. Therefore, in conclusion the climatic conditions similar to Granada, which are 18/13 °C day/night, a VPD close to 0.5 KPa, and radiation that did not exceed 1000 μmol photons/m2s favored the good physiological performance of gulupaDesempeño fotosintético y potencial hídrico foliar de gulupa (Passiflora edulis Sims, Passifloraceae) en estado reproductivo en tres localidades de los Andes colombianos La gulupa, Passiflora edulis Sims (Passifloraceae) es un frutal importante debido a sus características organolépticas, nutricionales y su demanda en el mercado internacional; sin embargo, existen muy pocos estudios relacionados con su ecofisiología. Hasta el momento, el cultivo se ha extendido a través del país por medio de conocimiento empírico sin tener datos que sustenten las zonas más apropiadas para su cultivo. Por esta razón, en el presente estudio se midió el intercambio de gases, la fluorescencia de la clorofila (factor de eficiencia del fotosistema II y eficiencia cuántica fotoquímica máxima del fotosistema II) y el potencial hídrico foliar en tres localidades diferentes del departamento de Cundinamarca (Chía [2610 m s.n.m., 14 °C], Granada [2230 m s.n.m., 15 °C] y Tena [2090 m s.n.m., 17 °C]), cuyas condiciones climáticas fueron monitoreadas con estaciones meteorológicas para evaluar  el desempeño fisiológico en cada localidad  y relacionarlo con los factores ambientales. Los resultados indican que aunque la capacidad fotosintética fue alta y similar en Granada y Tena, el estado hídrico de la planta, el control estomático de la pérdida de agua y la recuperación de los fotosistemas durante la noche fueron más eficientes en Granada (p 0.05). En Tena, la estrecha diferencia entre los valores día/noche de temperatura, humedad y déficit de presión de vapor (DPV) limitaron la recuperación hídrica de la planta, mientras que en Chía el aumento de DPV en el día, y las bajas temperaturas disminuyeron el potencial hídrico, tanto durante el día como durante la noche, así como la recuperación del fotosistema II. Por tanto, en conclusión, condiciones climáticas cercanas a las de Granada; 18/13 °C día/noche, DPV de 0,5 KPa, y una radiación que no exceda los 1000 μmol fotones/m2s favorecen el buen desempeño de la planta.